Empowerment and Conservation Action through the Planting of Million Tree Onthe Banks of Limboto Lake in Buhu Village, Telaga Biru Sub- District, Gorontalo Regency - Trisusanti Lamangida; Talha Dangkua (Journal of Universal Community Empowerment Provision, 2021)
The aim of this program is the action of Community Development through planting a million trees on the banks of Limboto lake in Buhu village, Telaga Biru sub-district, Gorontalo Regency. This program is carried out as an effort to conserve the damage of the Limboto lake ecosystem, collaboration with the Universitas Muhammadiyah Gorontalo, the government of Buhu village and the community of Buhu village. The method used in this activity is the method of socialization and the implementation of planting a million trees on the banks of Limboto lake. The flow of this activity includes the preparation of field observations and implementation of planting a million trees on the banks of Limboto lake. The results and discussion show that the empowerment action and the planting of a million trees on the banks of Limboto lake going well. It was concluded that the community empowerment action and conservation efforts through the program of planting a million trees on the banks of the Limboto lake have not been able to attract sympathy from the coastal communities of Limboto Lake. It is suggested to the government of village that empowerment actions and conservation efforts for Limboto lake like this need to be cultivated to a broader level of community understanding, about the need for action and actions to preserve Limboto lake through community empowerment programs.